Juridical Analysis of Legal Protection On Charges Due To Discretionary Authority For Regional Officials - Untung Saritomo; Riswadi Riswadi (Journal Research of Social Science, Economics, and Management, 2024)
This article reviews the roles and responsibilities of local officials in the use of discretionary powers and the legal repercussions that may arise from their decisions. Through a juridical approach, it investigates the legal protections available to local officials when they face indictments or lawsuits as a result of their discretionary actions. Taking into account the existing legal framework, this article analyzes various factors that may influence whether local officials will be held legally responsible for their discretionary decisions, including ethical, public policy and fairness considerations. In addition, it explores the legal safeguards that local officials can take, including enforceability of laws, liability insurance, and dispute resolution mechanisms. As such, this article aims to provide a better understanding of the complexities of legal protection for local officials in the context of the use of discretionary authority. The results showed that legal protection for regional officials related to the use of discretionary authority can be seen from various aspects, including the principle of legality, the principle of legal certainty and accountability. The juridical analysis of legal protection against charges due to discretionary authority for regional officials shows the importance of a deep understanding of the limits and responsibilities attached to the use of such authority. By paying attention to aspects of legality, legal certainty, and accountability, it is hoped that legal protection for regional officials can be guaranteed in the context of the use of discretionary authority.